Growing Up Catholic in a Scottish City: The Relationship Between Denominational Identity, Denominational Schools, and Attitude Toward Christianity Among 11- to 15-Year-Olds - Francis, Leslie J.; Gibson, Harry M. (Catholic Education: A Journal of Inquiry and Practice, 2001)
From a large survey conducted in a Scottish city, this article identifies 1,285 students attending Catholic schools (16.6% of whom were not Catholics) and 1,240 Catholic students (14.8% of whom were educated in non-Catholic schools). The data demonstrate that Catholic students educated in Catholic schools hold a more positive attitude toward Christianity than comparable Catholic students educated in non-Catholic schools and that non-Catholic students educated in Catholic schools hold a less positive attitude toward Christianity than comparable Catholic students. Both findings have implications for the evaluation of the Catholic school system.